The Effect of Communication, Fund Disbursement, and Competence on Trust, Attitudes, and Behavioral Intentions towards ZIS Institutions - Deni Nuryadin; Indupurnahayu; Didin Hafidhuddin; Irfan Syauqi Beik (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Zakat, Infaq, and Alms (ZIS) Management Institutions rely heavily on public trust to ensure sustainable long-term support. Despite its importance, the existing literature still lacks an integrated model linking organizational operational performance with stakeholder behavioral outcomes. This study aims to assess how institutional practices, including communication, perceived competency, and disbursement, influence trust and subsequently affect stakeholder attitudes and behavioral intentions toward ZIS institutions. This study uses a quantitative approach with a causal-descriptive design. Data were collected through a survey of ZIS Institution stakeholders and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that trust is a central factor that significantly shapes stakeholders’ attitudes and behavioral intentions. Specifically, perceived competence is the strongest and most significant predictor of trust. In contrast, the fund disbursement variable was found to be insignificant in building trust. Trust has significant predictive power in shaping attitudes, but its influence on behavioral intentions is moderate. The main contribution of this study is to provide empirical evidence that ZIS institutions’ efforts should focus on improving managerial competence and professionalism, not just on the fund distribution process, as a strategic key to increasing public trust.